A tragédia anunciada da barragem de Pedreira (SP): conflitos territoriais e ambientais na produção de um espaço de risco - Sandonato, Diogo Loibel (Universidade Federal de São Carlos, 2023)
The present work addresses the production of a risk space generated by the construction of a dam in Pedreira/SP and the environmental and territorial conflict generated by it. To this end, the thesis aims to analyze the contributions of Henri Lefebvre's theory of space production (2006; 2013) to understanding the conflict generated by the production of this risk space. Starting from the approach of this theory with the fundamental elements for understanding territorial and environmental conflicts, we analyze how risks are conceived, perceived and experienced by the population of Pedreira. We analyzed how it was possible for such a dam to be designed and licensed, producing risks and how there is a dispute posed by the definition of who is affected by this major project. We also address how the social construction of risk perception related to the dam occurs and the dynamics of mobilization and demobilization related to this perception. These risks are represented, involving the fundamental information for whether they are recognized or not. They are also physically perceived, involving seeing, hearing, and feeling the impacts and potential threats generated, as well as associating the production of these risk spaces with previous experiences. In other words, the risks are experienced and are related to the history, memory and belonging of the affected territories, as well as the daily lives of those who live with threats that have the potential to generate illness, impacts on the psychosocial dimension. In this conflict, the definition of who is considered affected is fundamental, influencing both the licensing of the project and also the possibilities for reparation and recognition of rights. In Pedreira, the population that has an appropriation of space, memory, history and belonging is affected by the production of a risk space by the dam. A conflict experienced, in which the population is subject to conceiving the risk based on the dispute over information that is or is not shared about the insecurity produced, to perceiving the risk based on the impacts of a major development project that changes the dynamics of the territory and access to goods such as water, and living with risk based on previous and current experiences of life on the banks of the Jaguari river. These experiences can intensify territorial and environmental conflicts as they attempt to combat the production of this risk space or at least build strategies to protect against the risks posed. Through this case, we assess the potential contributions of Lefebvre's theory and point out possible enhancements and developments for the analysis of territorial and environmental conflicts and the production of risk spaces.
The announced tragedy of the Pedreira dam (SP): territorial and environmental conflicts in the production of a risk space
La tragedia anunciada de la presa de Pedreira (SP): conflictos territoriales y ambientales en la producción de un espacio de riesgo
Keywords: Barragem; Água; Conflito territorial; Conflito ambiental; Pedreira/SP; Lefebvre; Produção do espaço; Risco; Dam; Water; Territorial conflict; Environmental conflict; Space production; Risk; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA; OUTROS::CIENCIAS